PENTINGNYA PENDIDIKAN ORANG TUA DALAM MENUNJANG PERKEMBANGAN ANAK USIA DINI - Nuroh, Siti (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
Parental education plays a crucial role in stimulating early childhood development, particularly in cognitive, socio-emotional and language aspects. This study aims to analyze the relationship between parental education levels and early childhood development stimulation. The research employs a quantitative method under descriptive approach. The sample consists of early childhoods’ parents selected using disproportionate stratified random sampling. Data were collected through questionnaires and analyzed using the Pearson Product Moment correlation test. The results of the study indicate that the higher level of parental education, the more optimal the stimulation provided. Other factors, such as economic conditions and access to information also affect the effectiveness of stimulation. This study concludes that parental education is the main factor to support optimal early childhood development.